Teaching controversial issues: A European perspective - Berg, Wolfgang; Graeffe, Leena; Holden, Cathie (2003)
Introduction: This guidance has been written by teacher educators from England, Finland and Germany where education for citizenship is seen as important but is approached in different ways. For example in Finland the debate is around values and equality, in the particular context of an emerging multi-cultural society. In England, education for citizenship has been made statutory for English secondary schools from September 2002, and recommended for primary schools. Other European countries are also re-thinking these aspects of their education system. In France, education civique, juridique et sociale (ECJS) has been introduced for all secondary pupils, with the emphasis being on social issues and 'real' political problems, which marks an important departure in a country where there is a strong tradition of neutrality in schools (Tutiaux-Guillon 2001). This is not a phenomenon restricted to schools in Europe, however. The need for such education has been debated (and implemented) in many other countries, including Australia, Canada and the United States. The inclusion of discussion of controversial issues- in terms of methodology and content- appears central to effective education for citizenship.